Abdominoscrotal hydrocele with ipsilateral hydroureteronephrosis in an adult: A case report (Indian Journal of Case Reports, 2024)
Abdominoscrotal hydrocele (ASH) is very rare in adults and difficult to suspect on clinical examination. ASH is a very unusual presentation of scrotal hydrocele with extension intra-abdominally through the inguinal canal either communicating to the peritoneal cavity or non-communicating. An ASH is a congenital pathology involving a scrotal hydrocele expanding through the inguinal canal and reaching the abdominal cavity. Here, we present the case of a 25-year-old man admitted with a complaint of pain and lump in the left lower abdomen for 2 months and swelling in the left groin for 2 years. Ultrasound and computed tomography suggest left ASH with left- sided hydroureteronephrosis. A left DJ stent was placed and on exploration, a large cystic mass was seen intraperitoneally extending into the scrotum through the inguinal canal. Excision of the abdominal part and partial excision of the scrotal part were done with eversion of the remaining tunica vaginalis sac. Although ASH is a rare entity, it should always be kept on the list of differential diagnoses during the complaint of large abdominal mass in adults.